A killer edition - Barrett, Lorna (A booktown mystery, 2019)
With her assistant, Pixie, picking up more responsibility around the shop, Tricia Miles suddenly has a lot more time on her hands. Tricia decides to join the local animal-rescue board and enter the Great Stoneham Bake-Off, but neither pans out as smoothly as she'd hoped. Balancing a bake-off that's heating up with a frosty reception from the board, Tricia stops by Joyce Whitman's romance bookstore looking for a book to get her fired up. She stumbles on something hot, but it's an argument between Joyce and her neighbor Vera Osborn instead of a steamy read. When Vera turns up dead in Joyce's garden hours later, Tricia has to wonder--could Joyce be the killer? Or is the culprit still lurking in town? One thing is for sure, someone in Stoneham is stirring up something more sinister than sweet. Tricia is determined to win the cutthroat cooking contest, but first she will have to make sure no one else is in danger of getting burned....